Development of a methodology for choosing conditions of interaction between harvesting and transport complexes - Muzylyov, Dmitriy; Kravcov, Andrey; Karnaukh, Mykola; Berezchnaja, Natalija; Kutya, Olesya (Eastern-European Journal of Enterprise Technologies, 2016)
The study suggests a method of forming the structure of harvesting and transport complexes by an example of the most common models of combine harvesters, means of mechanization as well as machines and technologies used in harvesting grain crops. The optimum stock of harvesting machinery and vehicles was determined by using a complex nomogram of their interaction conditions. An integral criterion of forming the structure of the complex was based on the measure of the technical features of an agricultural enterprise, the technological parameters of harvesting machinery, as well as the technical and economic performance of harvesting machines. A nomogram was built to determine the minimum cost of transporting one ton of grain, taking into account not only the operating costs but also the principle of logistics performance of both the combine harvester and the correctly chosen truck. The nomogram was developed to ensure complete coordination in the work of the whole harvesting and transport complex. The structuring of the existing classes of combine harvesters was substantiated to categorize them into three groups, taking into account the working width of the header and the area of agricultural land. The suggested classification can be used to choose from a set of alternatives one of the considered transport-technological complex patterns on the basis of minimum costs.